Immunological Effects of Ceramic and Composite Subgingivally Extended Restoration - Bilal Mohammed Obaid (Journal of Global Pharma Technology, 2019)
In this study, 80 samples of gingival crevicular fluid (GCF) from patients have their teeth filled with different restoration materials , collected 20 sample of composite resin restoration material ,20 sample of crown ceramic restoration material , 20 sample of metal ceramic restoration material and 20 sample of control non-filled teeth. The purpose of this study was determine the effects composite rein , ceramic crown and metal ceramic crown restoration material on (GCF) levels of interleukin 1(IL-1 β) ,  interferon gamma (IFN- γ) , Matrix Metalloproteinase-8 (MMP8) and tumor necrosis factor (TNF- β ). Paper points (size 30) were inserted into the gingival crevice until mild resistance was felt, and kept in place for 30 seconds. Following collection of GCF the paper point placed in eppendroffs tubes contain (300 micro liter) phosphate buffer saline. GCF was eluted from paper point by centrifugation at 3000 rpm for 15 minutes after that the paper point was removed and GCF sample kept at -40 ˚C till analysis. Analysis of data for immunological parameter (IL-1β, IFN- γ, TNF- β and MMP8) that got from ELISA test. Finally, the results showed mean concentration of  IL-1β, IFN- γ, TNF- β and MMP8 in patients with restoration material ( composite resin , crown ceramic and metal ceramic) significant (P < 0.05) were higher than in control while MMP-8 in ceramic crown restoration material  high but no significant (P> 0.05 ).Keywords: Composite resin, Ceramic crown, Metal ceramic crown, Periodntitis IL-1β, IFN- γ, TNF- β, MMP8.